Karakteristik Biologi Populasi Kerang Sepetang (Pharella acutidens) di Ekosistem Mangrove Dumai, Riau - Efriyeldi Efriyeldi; Dietriech G Bengen; Ridwan Affandi; Tri Prartono (Fakultas Perikanan dan Kelautan, Universitas Riau, 2012)
Characteristic of population biology of the “sepetang” clam has been studied inDumai mangrove ecosystem from November 2010 to October 2011. This researchwas to study the patterns of the population growth, mortality and recruitment ofthe clam P. acutidens. Sampling was monthlyfrom plot 1 m x 1 m quadratictransects. The result showed that growth pattern of P. acutidens was negativeallometric with asymptotic length (L∞) 92.71 mm.The annual growth coefficient(K) and total mortalitywere 0.59 and 1.87 per year, respectively. The naturalmortality was probably related to environmental condition. The recruitmentoccurred every month, the peaks occurred on April (15.93%) and August(13.16%).